STRUKTUR KEPEMILIKAN, KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG - Trisnabudi, Ardian Noor; Fitria, Astri (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of the ownership structure and dividend policy to the firm value with the debt policy as the moderating variable on the Food and Beverages which are listed in Indonesia Stock Exchange in 2011-2013 periods. The samples are 10 Food and Beverages companies which are listed in Indonesia Stock Exchange (IDX) and the observation numbers are 30 and they have been selected by using purposive sampling. The hypothesis test has been done by using multiple linear analyses in order to test the influence of ownership structure and dividend policy to the firm value and the debt policy as the moderating variable on the Food and Beverages Companies. In this research, the ownership structure has been measured by using managerial ownership (KM), domestic institution ownership (KID), foreign institution ownership (KIA), public ownership (KP); dividend ownership has been measured by using dividend payout ratio (DPR); debt policy has been measured by using debt ratio to the equity (DER), and firm value (NP) has been measured by using price to book value (PBV) variable. The result of multiple linear regressions shows that ownership structure and dividend policy have influences to the firm value. Meanwhile, the analysis of moderating variable which is done by using interaction test of moderated regressions analysis (MRA) method shows that the debt policy moderates the influence of ownership structure and dividend policy to the firm value.Keywords: Ownership Structure, Dividend Policy, Companyâs Debt Policy.